Laparoscopy versus ultrasonography for the evaluation of Müllerian duct remnants in male patients with disorder of sex differentiation - Mohamed Sayed Abd El-Monsif; Noha Arafa; Mahmoud Marei Marei; Gamal Eltagy; Ahmed M. K. Wishahy (SpringerOpen, 2024)
Abstract Background The diagnosis of male differences of sex development is a challenging multidisciplinary team task, that requires external genital evaluation, karyotyping, hormonal profiling, radiological work up and frequently diagnostic laparoscopy and biopsy, for evaluation of internal duct system and nature of gonads. The debate still persists regarding the best diagnostic modality for accurate visualization of Müllerian duct remnants (MDRs) in those patients. The aim of the study was to compare between laparoscopy (L) and ultrasonography (US) regarding the diagnostic accuracy in detection of Müllerian duct remnants, in addition to describing their anatomical nature and relations with the male duct system, in patients with male DSD, with various karyotypes. Methods We prospectively included 20 patients with male DSD, mostly due to 46 XY DSD or chromosomal DSD, over 2 years. The medical and radiological data were collected and analyzed. Results The age at the first diagnostic intervention ranged from 8 to 24 months (mean: 17 months). There were 14 patients with 46XY DSD with variable diagnoses (3 ovotesticular DSD, 3 partial gonadal dysgenesis, 6 persistent Müllerian duct remnants syndrome and 2 mixed gonadal dysgenesis). Two patients with 46XX DSD were included (one XX male, and one patient with ovotesticular DSD). One patient with chimerism (46XY/46XX) and three patients with 46XY/45XO mixed gonadal dysgenesis were also recruited. MDRs were evident in all cases (100%) by laparoscopy, only 25% (n = 5) were visualized by US. There was a statistically significant difference between laparoscopy and US regarding gonadal and MDR visualization, being higher with laparoscopy (p values, 0.0180 and 0.001). Conclusions Ultrasonography failed to visualize Müllerian remnants in 75% of patients with complex DSD. On the other hand, laparoscopy provided optimum visualization of MDRs and gonads in those children.